Imperialism and transitions to socialism - Herrera, Rémy (Research in political economy., 2021)
This collection of essays is designed to shed light on the issues of imperialism and the transitions to socialism. Written by eighteen contributors, from twelve countries and three continents, it is organized into two main parts. The first section delves into the theoretical aspects, the analysis of which is key for understanding the subject under consideration. The second part of the volume is focused on the examination of practical experiences of socialist transition, more or less advanced and with varying degrees of success, in China, Vietnam, North Korea, Cuba, Venezuela, Ecuador, and Brazil. Imperialism and Transitions to Socialism argues that countries wanting to embark on a socialist transition is not only a response to a spirit of justice, but also an answer to the call of reason: it is a question of survival for humanity, and for life. Socialism is not just a word, it is a struggle. It is not an end, but a transition process, long and difficult, that can take many paths towards the liberation of labour from the domination of capital. It is socialism, a society of solidarity, which walks with history.